2014
DOI: 10.1371/journal.pone.0109713
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiles in Acute Respiratory Distress Syndrome Differentiates Survivors from Non-Survivors

Abstract: Acute Respiratory Distress Syndrome (ARDS) continues to have a high mortality. Currently, there are no biomarkers that provide reliable prognostic information to guide clinical management or stratify risk among clinical trial participants. The objective of this study was to probe the bronchoalveolar lavage fluid (BALF) proteome to identify proteins that differentiate survivors from non-survivors of ARDS. Patients were divided into early-phase (1 to 7 days) and late-phase (8 to 35 days) groups based on time aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 62 publications
3
45
0
Order By: Relevance
“…While most studies have targeted a pre-determined biomarker, several investigators have examined proteomic changes in BALF samples from ARDS patients using a non-targeted approach (64)(65)(66). These non-targeted proteomic studies compared the protein levels in the BALF or undiluted pulmonary edema fluid in ARDS patients and in healthy controls.…”
Section: Non-targeted Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…While most studies have targeted a pre-determined biomarker, several investigators have examined proteomic changes in BALF samples from ARDS patients using a non-targeted approach (64)(65)(66). These non-targeted proteomic studies compared the protein levels in the BALF or undiluted pulmonary edema fluid in ARDS patients and in healthy controls.…”
Section: Non-targeted Proteomicsmentioning
confidence: 99%
“…Ideally, BALF proteomics could be useful for the molecular profiling of DAD. For example, Bhargava et al (66) examined BALF from patients with different severities of lung injury, and identified 792 proteins, from which 161 were differentially expressed in survivors and non survivors in the early phase of ARDS. Pathways related to activation of immune response, wound healing and coagulation were predominant in survivors, while pathways of collagen synthesis and carbohydrate catabolism were more abundant in non-survivors.…”
Section: Non-targeted Proteomicsmentioning
confidence: 99%
“…Graft sources included bone marrow (1), peripheral blood stem cells (6), umbilical cord blood (18) and natural killer cell (3). All BALF samples were collected from clinically indicated bronchoscopies performed using a standard protocol [18, 19] with excess, cell-free supernatant used for these studies. The diagnosis of IPS or infectious lung injury was made using the criteria established by the American Thoracic Society [6] (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…BALF samples containing at least 1.2 mg of proteins were processed for LC-MS/MS from individual patients employing a protocol previously published with minor modifications [18]. BALF was concentrated and desalted using Amicon 3-MWCO filters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation